HUBUNGAN FILSAFAT, TEORI BELAJAR DAN KURIKULUM PENDIDIKAN - Tio Ari Laksono; Muhammad Akhsanul Muhtadin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The educational process from the viewpoint of the mainstream educational philosophy requires that students be able to use their abilities constructively and comprehensively to adjust to the demands of scientific and technological developments. students must actively develop knowledge, not just wait for directions and instructions from the teacher or fellow students. Educational institutions must be developed and managed properly, effectively, and efficiently. To manage and develop educational institutions so that they become better quality, and have high competitiveness can be based on the law of causality or cause and effect as a foundation for building enthusiasm so that they can work hard to achieve the vision and mission of the institution. The method used in this study uses a library method or approach (library research), Literature or literature study can be interpreted as a series of activities related to library data collection methods, reading and recording, and processing research materials. Philosophy is a science that can support all aspects of science because when someone philosophizes, that person will think broadly and have many references to knowledge. So that in determining and designing a curriculum, philosophy is needed so that what will be achieved from the curriculum can be fulfilled. In developing an educational curriculum, it is required to know some of the right foundations to determine a step for making a curriculum, the foundations in educational philosophy are divided into 3, namely; ontology, epistemology, and axiology. So the curriculum is made to clarify all forms of learning activities to achieve educational goals.